Using of morphological theory to improve English reading comprehension ability of EFL students - Moendee, Rungnapa; Suphat Sukamolson; Suwaree Yordchim (Journal of English Language and Linguistics, 2024)
This study aimed to 1) explore the English reading comprehension problems and needs of EFL students, 2) construct the English reading comprehension handbook by using morphological theory to improve their English reading comprehension ability, and 3) evaluate the effectiveness of the English reading comprehension handbook that uses morphological theory. The population consisted of 128 first-year EFL students who had taken the BRU English proficiency test and experienced difficulties with English during the 2023 academic year. From this population, a sample of 30 participants was selected using systematic sampling techniques. The study used several research instruments to collect data which included: 1) a questionnaire to identify the problems faced by students in comprehending English reading, 2) an English reading comprehension handbook by using morphological theory, 3) pre-test and post-test, and 4) a questionnaire assessing students’ satisfaction with the English reading comprehension handbook that uses morphological theory. The results revealed that 1) most EFL students acknowledged facing challenges in English reading comprehension, with vocabulary knowledge receiving the highest, followed by fundamental knowledge, and knowledge of sentence structure, respectively. Moreover, the students express a high-level need to improve their English comprehension using morphological theory, 2) The handbook is structured into five chapters, each rooted in morphological theory to offer through assistance for students facing challenges in English reading comprehension, and 3) The English reading comprehension handbook, which utilized morphological theory, received the highest level of student satisfaction and students demonstrate higher English proficiency test scores after utilizing the English.